Student Assistance Program Outcomes for Students at Risk for Suicide - Biddle, Virginia Sue; Kern, John; Brent, David A.; Thurkettle, Mary Ann; Puskar, Kathryn R.; Sekula, L. Kathleen (The Journal of school nursing, 2014)
Pennsylvania’s response to adolescent suicide is its Student Assistance Program (SAP). SAP has been funded for 27 years although no statewide outcome studies using case-level data have been conducted. This study used logistic regression to examine drug-/alcohol-related behaviors and suspensions of suicidal students who participated in SAP. Of the 46 services, 10 best predicted (p < .01) that these undesirable outcomes would cease. Although no study subjects died by suicide, 42 of 374,626 referred students did die by suicide. Suicidal students who did not participate had double the rate of suicide of suicidal participants of SAP. Students referred for other reasons also killed themselves. Further work must be done to assess all referred students for suicide risk, examine educational outcomes, monitor substance-related crimes and overdoses, and examine school-related factors postmortem. Evidence from this study can be used by researchers to plan future studies and by Pennsylvania’s school nurses when planning services.